Isolation and Quantification of Lactic Acid Bacteria from Traditional Fermented Products in Benin - TCHEKESSI, C. K. Célestin; BOKOSSA YAOU, Innocent Padonou; AZOKPOTA, PAULIN; AGBANGLA, CLÉMENT; DAUBE, Georges; SCIPPO, Marie-Louise; KORSAK, Nicolas; GOTCHEVA, Volcheva; BLAGOEVA, Ginka; ANGELOV, Angel (My University, 2014)
In Africa, fermented food products are particularly used as weaning foods for young children, pregnant women and the seniors. In Benin, most of these cereals-based foods are manufactured and sold around the streets. These are ablo, dèguè, akpan, abotin, gowé etc ... This study focused on the isolation and enumeration of bacteria and yeast from twenty six (26) samples of traditional African fermented foods. Decimal dilution method allowed us to isolate a total of 42 different strains of microorganisms among which we counted 30 lactic acid bacteria. They confirmed their biological potential by expanding in selective medium MRS. When they were then subjected to screening, the medium of MRS-broth-starch agar, and eight (08) of the isolated strains tested showed their characters of amylolytic strains. The eight strains isolated were tested and finally cultivated at temperatures and pH ranging respectively from 30°C to 60°C and 3.0 to 6.5. These eight (08) amylolytic lactic acid bacteria (ALAB) synthesized enzyme amylase both inside and outside the bacterial cell with a very interesting activity value. The temperature limit between 40 and 45°C is best for the bacteria 26.2, B16 and B18 while the optimum pH for amylase synthesis is between 4.0 and 4.5 for the same microorganisms that have given the largest values of enzyme activity. The best strains 26.2, B16 and B18 secrete more enzymes in extracellular medium than intracellular.
Keywords: Fermented products; lactic acid bacteria; isolation; quantification